Spatial and Seasonal Distribution of Cadmium and Lead in Sediment, Water and Its Response of Metal Transcription Factor-1 in Cardinal Fish Apogon beauforti - Dominggus Rumahlatu; Estevanus Kristian Huliselan; Sriyanti Imelda A Salmanu (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2018)
Cadmium (Cd) and lead (Pb) are known to have high toxic effects and have been found polluting marine environment. Regular monitor the concentration of heavy metals in marine waters is necessary by combining chemical and biological analysis.  This research was conducted to analyze the levels of heavy metals in sediment, water column, cardinal fish Apogon beauforti, and to measure the concentration of MTF-1 protein in A. beauforti. This research was conducted at four sampling stations at Ambon bay for 2 years. The levels of Cd and Pb metals were analyzed using AAS instruments (Atomic Absorbsion Spectrophotometer), while the concentration of MTF-1 protein in the body of A. beauforti was analyzed using indirect ELISA. The results showed that the seasonal and spatial distribution of heavy metals Cd and Pb at Ambon bay did not show any variation. The results of the ANOVA proved that the concentrations of heavy metals Cd and Pb in the four research stations were not significantly different in the year 2013 and in the year 2014 in the samples of sediment, the water column, and the body of A. beauforti. In addition, it was revealed that the concentration of MTF-1 protein of A. beauforti in 2014 was higher than that in 2013, with an average of the concentration of MTF-1 protein of A.beauforti was higher at station 2, which was at Ferry Galala Harbor. Keywords: distribution, spatial, seasonal, cadmium, lead, MTF-1, Apogon beauforti